Screening and Estimation of Bioactive Compounds of Azanza garckeana (Jakjak) Fruit Using GC-MS, UV–Visible Spectroscopy, and HPLC Analysis - Abdalrhaman M. Salih; Fahad Al-Qurainy; Mohamed Tarroum; Hassan O. Shaikhaldein; Abdulrahman Hashimi (Separations, 2022)
Azanza garckeana (F. Hoffm). Exell and Hillc. is an important food and medicinal plant that has been used in tropical Africa. Therefore, this study aimed to investigate the nutritional value of jakjak fruit using different analytical techniques. The obtained results have demonstrated that jakjak fruit is very rich in total soluble sugar, constituting about 48% of the dry weight. Moreover, the chromatographic analysis revealed that jakjak fruit contained a high amount of glucose, fructose, maltose, and ascorbic acid. Further, GC-MS analysis detected four compounds related to secondary metabolites. Some of these detected constituents have medicinal value. For example, phenol, 2,4-bis (1,1-dimethylethyl) has been reported to have many functions such as antioxidant activity, anticancer, antifungal, and antibacterial properties. Furthermore, the antioxidant potential of different concentrations of deionized water and methanolic extracts was estimated using 2,2-diphenyl-1-picrylhydrazyl (DPPH). The results showed that the scavenging activity of the DPPH radical was found to be raised with increasing concentrations of fruit extracts. The concentration (50%) of both methanol and deionized water gave the best inhibition percentage (91.7 and 84.4%), respectively. In contrast, the methanolic extract has shown significant results compared to deionized water. This study concluded that jakjak fruit is very rich in total soluble sugar and phenolic compounds, which can be used as a source of polysaccharides and antioxidants for the human diet as well as raw materials for downstream industries.